FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI TERHADAP PEMILIHAN KARIR AKUNTAN PUBLIK (Studi Kasus pada Mahasiswa Jurusan Akuntansi pada Sekolah Tinggi Ilmu Ekonomi Pontianak) - Yulius Paul Pian; Ika Nur Azmi Azhari; Marjono Marjono (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2022)
Purpose of this study was to determine the factors that influence the interest of accounting students in choosing a career as an accountant. public. The factors that influence the career choice of accounting students as public accountants are measured by financial awards, professional training, professional recognition, market considerations and as moderating variables. The sample in this study were students at the Pontianak School of Economics majoring in accounting. Data analysis used multiple linear regression analysis and random sampling technique with an absolute difference value approach. The results showed that labor market considerations, professional training, and professional recognition had a significant positive effect on the interest of accounting students in choosing a career as a public accountant. Financial rewards are able to moderate the effect of labor market considerations and professional recognition on the interest of accounting students in choosing a career as a public accountant. However, it is not able to moderate the effect of professional training on the interest of accounting students in choosing a career as a public accountant.